Influence of grains distribution on the rheological behavior of mortars. (20th July 2018) - Stolz, Carina M.; Masuero, Angela B.
Highlights: The influence of the granulometric composition of sand on rheological behavior of mortars is investigated. Rheological behavior of mortars is observed whit rotational rheometer and squeeze-flow tests. It is identified mortar flow is directly dependent on particle packing and uniformity index of the fine aggregate. Abstract: The objective of this study was to analyze the influence of different proportions of mortars and different granulometric compositions on the rheological behavior of these materials through squeeze-flow and rotational rheometry trials. To this end, mortars with proportions of 1:0:3, 1:1:6 and 1:2:9 (cement:hydrated lime:sand, in volume, dry materials) were produced. Each proportion was dosed with three different granulometric compositions (GC), produced in the laboratory. These mortars were subjected to characterization trials in the fresh state, in addition to rheological analysis by squeeze-flow and rotational rheometry. The results demonstrated that mortar flow is directly dependent on particle packing, in addition to the uniformity index of the fine aggregate. The proposed rheological trials were efficient in identifying the different rheological behaviors of the produced mortars.